1992
DOI: 10.2166/wst.1992.0431
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Nitrification and Denitrification in Micro-Aerobic Biofilms

Abstract: Simultaneous nitrification and denitrification (SND) occurs in a micro-aerobic biofilm. Using a partially submerged rotating biological contactor(RBC) whose air phase oxygen partial-pressure is controllable, an experimental investigation was made into the effects of the oxygen flux to the biofilm on the SND. The lower the oxygen flux the lower the nitrification efficiency and the higher the denitrification efficiency until the maximum nitrogen removal efficiency was obtained. The state was reached at an oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The effects of raw sewage C/N ratio variations in small community WWTPs are highlighted in [8][9][10], which also show the possible negative side effects of dissolved oxygen accumulation in the denitrification stage. In addition, in 2006, in a Life project, the EU emphasized the effects of sharp fluctuations in the quality of raw sewage on the efficiency of biological processes [11].…”
Section: Open Accessmentioning
confidence: 99%
“…The effects of raw sewage C/N ratio variations in small community WWTPs are highlighted in [8][9][10], which also show the possible negative side effects of dissolved oxygen accumulation in the denitrification stage. In addition, in 2006, in a Life project, the EU emphasized the effects of sharp fluctuations in the quality of raw sewage on the efficiency of biological processes [11].…”
Section: Open Accessmentioning
confidence: 99%
“…In this way, their growth was attributed to soluble microbial products release by autotrophic. (Watanebe et al, 1992;Rittmann and Snoeyink, 1984). From these values, it can be observed that heterotrophic bacteria present a high growth rate in relation to nitrifying autotrophic.…”
Section: Heterotrophic Bacteriamentioning
confidence: 95%
“…The application of Submerged Aerated Filters (SAFs) for wastewater treatment has been more successful for the removal of recalcitrant organics, suspended particles, phosphorus and nitrification/denitrification than conventional trickling filters (Chen et al 1991;Masuda et al 1991;Watanabe et al 1992). The filter medium in SAFs is as important as in trickling filters to support and retain the growth of the biofilm and maximise organic and nutrient removal.…”
Section: Introductionmentioning
confidence: 99%